2002
DOI: 10.1097/00006254-200209000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Male Circumcision, Penile Human Papillomavirus Infection, and Cervical Cancer in Female Partners

Abstract: Background It is uncertain whether male circumcision reduces the risks of penile human papillomavirus (HPV) infection in the man and of cervical cancer in his female partner. Methods We pooled data on 1913 couples enrolled in one of seven case-control studies of cervical carcinoma in situ and cervical cancer in five countries. Circumcision status was self-reported, and the accuracy of the data was confirmed by physical examination at three study sites. The presence or absence of penile HPV DNA was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
178
2
15

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(205 citation statements)
references
References 31 publications
(51 reference statements)
10
178
2
15
Order By: Relevance
“…In two reports, Castellsagué et al (1997Castellsagué et al ( , 2002 Although our results showed that 50% of the infected couples presented the same HPV types in CIN group, and were, then, higher than the ones published, we believe that the 50% disagreement in infecting types is due to such differences in the genital tract of men and women (Table 3). On the other hand, 50% of agreement among sexual partners leads us to suggest a vicious circle of infections among couples, perpetuating HPV in this group.…”
Section: Discussioncontrasting
confidence: 65%
“…In two reports, Castellsagué et al (1997Castellsagué et al ( , 2002 Although our results showed that 50% of the infected couples presented the same HPV types in CIN group, and were, then, higher than the ones published, we believe that the 50% disagreement in infecting types is due to such differences in the genital tract of men and women (Table 3). On the other hand, 50% of agreement among sexual partners leads us to suggest a vicious circle of infections among couples, perpetuating HPV in this group.…”
Section: Discussioncontrasting
confidence: 65%
“…This low DNA quantity is further reflected by the relatively high number of ␤-globin PCR-negative penile swabs (i.e., 24%) found in the present and another study. 16 As a consequence, defining HPV clearance in males was complicated. Analyses of viral clearance (defined as 2 consecutive negative HPV tests), restricted to men who were HPV-positive at baseline, showed that the HPV clearance rate was higher in the condom group compared to the noncondom group, though significance was not reached due to the low number of men analyzed [2-year rate of viral clearance was 27% in the condom group (n ϭ 26) vs. 7% in the noncondom group (n ϭ 15), p ϭ 0.2].…”
Section: Influence Of Hpv Status On the Clinical Course Of Flat And Pmentioning
confidence: 99%
“…Compared to uncircumcised men, Castellsagué et al 16 found a reduced risk of penile HPV infection among circumcised men and, in the case of a history of multiple sexual partners, a reduced risk of cervical cancer in their current female partners. The authors argue that the penile shaft and the outer surface of the foreskin are covered by keratinized, stratified, squamous epithelium, which provides a protective barrier against HPV infection.…”
Section: Influence Of Hpv Status On the Clinical Course Of Flat And Pmentioning
confidence: 99%
“…1 Circumcision is generally considered as a simple, rapid operation with efficacy for protection against HIV and other sexually transmitted infections, as confirmed in numerous, highquality studies. [2][3][4][5][6][7] Circumcision has been reported to adversely affect sexual function; 8 however, the majority of studies, including highquality ones [9][10][11] and ones with data arising from randomized controlled trials (RCTs), 12,13 show no difference or improvement in sexual function, sensitivity and satisfaction after circumcision. All of the data were considered by the American Academy of Pediatrics in formulating its 2012 policy, which concluded that there were no adverse effects on these parameters.…”
Section: Introductionmentioning
confidence: 99%